2020
DOI: 10.3390/polym12112679
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Plasma Polymerized 2-Ethyl-2-oxazoline Based Thin Films for Biomedical Purposes

Abstract: Polyoxazoline thin coatings were deposited on glass substrates using atmospheric pressure plasma polymerization from 2-ethyl-2-oxazoline vapours. The plasma polymerization was performed in dielectric barrier discharge burning in nitrogen at atmospheric pressure. The thin films stable in aqueous environments were obtained at the deposition with increased substrate temperature, which was changed from 20 ∘C to 150 ∘C. The thin film deposited samples were highly active against both S. aureus and E. coli strains in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…For the case of other geometries, Sneddon's model [71] and Oliver-Pharr model [69] are reported. The use of PeakForce Quantitative Nanomechanical Mapping (PF-QNM®, Bruker) [38] and nanoDMA [72,73] have been also reported. The latter allows the determination of the storage and loss moduli and consequently of loss factor.…”
Section: Measurement Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the case of other geometries, Sneddon's model [71] and Oliver-Pharr model [69] are reported. The use of PeakForce Quantitative Nanomechanical Mapping (PF-QNM®, Bruker) [38] and nanoDMA [72,73] have been also reported. The latter allows the determination of the storage and loss moduli and consequently of loss factor.…”
Section: Measurement Techniquesmentioning
confidence: 99%
“…The results showed that cell adhesion was favored in stiffer surfaces ( ∼ 120 MPa) when compared to softer ones ( ∼ 0.5 MPa). In recent works, plasma thin films with antibiofouling and antibacterial properties were shown to present excellent scratch and delamination resistance with polymer-like viscoelastic character [72,73].…”
Section: Applicationsmentioning
confidence: 99%
“…During the cleaning process, the high energy plasma level disrupted the structure of organic substances contaminating the material and removed impurities from the surface [130]. Plasma is also used in the industrial production of nanomaterials [131,132] and synthesis and application of thin coatings [133][134][135].…”
Section: Plasmamentioning
confidence: 99%
“…In our previous studies, POx thin coatings were deposited on glass substrates using plasma polymerization with 2-methyl-2-oxazoline or 2-ethyl-2-oxazoline vapor as a monomer [ 13 , 14 ]. The plasma polymerization was performed by means of dielectric barrier discharge burning in nitrogen at atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%